SINTESIS DAN KARAKTERISASI NANOPARTIKEL PERAK TERMODIFIKASI GLUTATHIONE MENGGUNAKAN REDUKTOR NaBH4 - Adrian Maulana Aditya; Daniel -; Noor Hindryawati (Jurusan Kimia FMIPA UNMUL, 2025)
Silver nanoparticles (AgNPs) possess remarkable properties that make them suitable for various applications in biomedical, environmental, and catalytic fields. This study focuses on the synthesis and characterization of glutathione-modified silver nanoparticles (AgNPs-GSH) using sodium borohydride (NaBH₄) as a reducing agent. The reduction of AgNO₃ by NaBH₄ produces elemental silver nanoparticles, as indicated by a color change to bright yellow due to the localized surface plasmon resonance (LSPR) phenomenon. The synthesized nanoparticles were stabilized using glutathione (GSH), which binds through thiol (-SH), amine (-NH₂), and carboxyl (-COOH) functional groups, enhancing the stability and biocompatibility of the AgNPs. UV-Vis spectroscopic analysis revealed a maximum absorbance at 408 nm, consistent with the optical properties of silver nanoparticles. Furthermore, particle size analysis indicated an average nanoparticle size of 1.271 nm, with some degree of agglomeration. These findings suggest the successful synthesis and functionalization of AgNPs-GSH with potential applications in nanobiotechnology.